Architectured microstructures in steel. (1st July 2014) - Anand, G.; Dey, P.; Kok, P. J. J.; Chakraborty, D.; Chattopadhyay, P. P.
Abstract: In the traditional physical metallurgy approach, the microstructure evolves as the product of the interactions between composition and process parameters, controlled by thermodynamic and kinetic conditions. Thus, the approach is more evolutionary than constructive. An architecturally designed microstructure implies planning, design and construction of microstructure considering nature, size, morphology and distribution of the constituent phases on a suitably conceived topological framework. This investigation puts emphasis on performance driven construction of the microstructure with precise calculation of response of microstructural constituents under the given loading conditions. With the aforesaid motivation, the present study elucidates the principle involving microstructural generation by Voronoi tessellation and subsequent elastoplastic finite element simulation. In addition, the present study also explores the correlation between architecturing and initiation of instability in the microstructure through genetic programming.